The role of possession of durable goods in gender-based developmentally-situated educational disparities in Colombia - Hans Walter Cabra Hernández; Jacobo Rozo Alzate (International Journal of Educational Research Open, 2024)
There is growing recognition that anti-poverty policies aimed at increasing access to assets, particularly durable goods, need to address the issue of gender-based developmentally-situated disparities. This study examined how different types of durable goods relate to academic achievement and school attendance in Colombia and whether this relationship varies by gender and school grade, expanding the geographic scope of existing literature on the subject to Latin America. Data for fifth and ninth-grade students with complete durable goods information (N = 364,436) from the 2017 SABER test, a nationwide examination that evaluates reading and math skills, were assessed using multilevel modeling. The results indicated that students whose families owned washing machines, computers or who had internet access performed better academically and were less likely to be absent from school, with larger effects for boys and fifth graders. This research contributes to the existing literature by illustrating the importance of durable goods on children's academic performance. The study recommends policymakers to support the formulation of asset-based policies that promote access to durable goods, particularly for girls and adolescents from low-income families.